2010
DOI: 10.1007/s11200-010-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Magneto- and biostratigraphy of the Jurassic/Cretaceous boundary in the Lókút section (transdanubian range, Hungary)

Abstract: Jurassic-Cretaceous sediments of Transdanubian Range in NorthernHungary mostly retain their primary magnetizations and are suitable for detailed bio-and magnetostratigraphic studies. The Lókút section, 13 m in thickness, is localized in the central part of the Transdanubian Range. It contains the Jurassic/Cretaceous boundary in pelagic carbonate facies. Although the colour of the rocks changes from reddish-pinkish in the bottom to almost white at the top of the section, magnetite was identified as a magnetic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 39 publications
4
29
0
Order By: Relevance
“…Higher up-section, a return towards more positive values up to 0.7‰ is observed. iostratigraphic data (Vigh, 1984;Főzy et al, 2011;rabowski et al, 2010a) together with magnetostratigraphic data (Grabowski et al, 2010a) allow us to accurately place the low point seen in the carbon isotope curve within these schemes. This minimum appears in the upper part of …”
Section: Stable Carbon and Oxygen Isotope Stratigraphymentioning
confidence: 99%
“…Higher up-section, a return towards more positive values up to 0.7‰ is observed. iostratigraphic data (Vigh, 1984;Főzy et al, 2011;rabowski et al, 2010a) together with magnetostratigraphic data (Grabowski et al, 2010a) allow us to accurately place the low point seen in the carbon isotope curve within these schemes. This minimum appears in the upper part of …”
Section: Stable Carbon and Oxygen Isotope Stratigraphymentioning
confidence: 99%
“…It should be noted that the magnetic susceptibility pattern across the J/K boundary is exactly opposite to that noted typically in the Tethyan sections. There is a general tendency of magnetic susceptibility decrease from the Upper Tithonian to Lower Berriasian strata; it is known from sections of Val Bosso (Houša et al 2004), Brodno (Houša et al 1996(Houša et al , 1999 Grabowski et al 2010). The opposite trend, observed in the Hlboča section only, is related to relative abundance of SP magnetite in the Padlá Voda Formation.…”
Section: Rock Magnetic Propertiesmentioning
confidence: 99%
“…Microbiostratigraphic callibration of Late Tithonian/Berriasian magnetozones was successfully performed in south Tethyan sections of the Apennines and Southern Alps Ogg et al 1991). Detailed magnetostratigraphic studies in the Apennines, Tatra Mts and Transdanubian Mts were published recently (Houša et al 2004;Speranza et al 2005;Grabowski & Pszczółkowski 2006;Grabowski et al 2010) and pilot results were reported from the Eastern Alps (Pruner et al 2009). The Brodno section in the Pieniny Klippen Belt (PKB) is currently proposed as the J/K regional stratotype in the Carpathians ).…”
Section: Introductionmentioning
confidence: 99%
“…Publications by Pálfy et al (2007) and Grabowski et al (2010) deal with geological correlation with the aid of palaeomagnetic polarity zones. Karátson et al (2007), Márton E (2007), Márton E et al (2007aMárton E et al ( , 2007b are concerned in correlation through the combination of palaeomagnetic marker horizons (which are the manifestations of dramatic changes in the orientation of the relevant tectonic unit) and polarity zones.…”
Section: Palaeomagnetismmentioning
confidence: 99%